2016
DOI: 10.1007/s00330-016-4660-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved image quality in abdominal CT in patients who underwent treatment for hepatocellular carcinoma with small metal implants using a raw data-based metal artifact reduction algorithm

Abstract: • SEMAR algorithm significantly reduces metallic artefacts from small implants in abdominal CT. • SEMAR can improve image quality of the liver in dynamic CECT. • Confidence visualization of hepatic vascular anatomies can also be improved by SEMAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In our study, we found improved image quality with reduced noise, improved CNR, less artifacts, and an improved visualization of stent patency on the CT images after SEMAR reconstruction in all target visceral arteries. Our findings are in agreement with prior studies on metal implants and embolization material, showing that SEMAR is effective in decreasing metal artifacts in single-energy CT images [ 8 , 9 , 13 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found improved image quality with reduced noise, improved CNR, less artifacts, and an improved visualization of stent patency on the CT images after SEMAR reconstruction in all target visceral arteries. Our findings are in agreement with prior studies on metal implants and embolization material, showing that SEMAR is effective in decreasing metal artifacts in single-energy CT images [ 8 , 9 , 13 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Various authors have proved the positive impact of SEMAR on metal artifact reduction in CT images of patients with orthopedic prostheses [ 14 , 15 ], embolization coils [ 8 , 9 , 15 ], and dental prostheses [ 13 ]. The impact of the SEMAR algorithm on CTA metal artifact reduction in patients after fenestrated and/or branched EVAR (F/B-EVAR) has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Single-energy metal artifact reduction (SEMAR, Canon Medical Systems Corporation, Ōtawara, Japan) is one of the many commercially available clinically used metal artifact reduction techniques [6] . SEMAR has proved to reduce metal artifacts in a range of clinical sites [7] , [8] , [9] , [10] , [11] . There are reports in the literature on improvements in CT number prediction and dose calculation accuracy by using SEMAR in carbon-ion therapy [12] , brachytherapy [13] , and EBRT [4] .…”
Section: Introductionmentioning
confidence: 99%